Computer graphics and urban archaeology Bracara Augusta’s case study - Bernardes, P. (2004)
Computer graphics is undoubtedly an important tool, widely used for representing and manipulating enormous amounts of highly complex information. Usually, the archaeological information is highly complex, so its representation using computer graphics technology is a true and engaging challenge. Virtual reconstructions representing archaeological sites, as for example the roman town Bracara Augusta, should be considered a fundamental tool for research improvement carried out by experts. It is also extremely important for the uprising consciousness of cultural heritage.